1999
DOI: 10.1038/sj.gt.3300802
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of tumor cell migration and metastasis by adenoviral gene transfer of plasminogen activator inhibitors

Abstract: Recombinant adenoviral vectors expressing u-PA, t-PA, virus expressing either PAI-1 or PAI-2 before implantation PAI-1 and PAI-2 were employed to correlate the significantly reduced the incidence of lung metastasis by expression of components of the fibrinolytic system with 60% compared with control virus. However, only PAI-2 the invasiveness of HT 1080 tumor cells. Migration through reduced the incidence of lung and brain metastasis followTranswell inserts in vitro in the presence of plasminogen ing liver gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
49
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 39 publications
10
49
0
Order By: Relevance
“…In a mouse model of acute myocardial infarction, blocking plasminogen activation by temporal infusion of PAI-1 prevented rupture of ventricular aneurysm (28), in which ventricular wall destruction by increased MMP activity is thought to be a main mechanism (29). It has also been shown that adenoviral transfer of the PAI-1 gene reduces tumor metastasis (30); in metastasis, extracellular matrix lysis is necessary for movement of transformed cells in tissues. In addition, Allaire et al have reported that, in a rat model of aortic aneurysm, blockade of PAs by local overexpression of PAI-1 prevents formation of aneurysms and arterial rupture by inhibiting MMP activation (9).…”
Section: Discussionmentioning
confidence: 99%
“…In a mouse model of acute myocardial infarction, blocking plasminogen activation by temporal infusion of PAI-1 prevented rupture of ventricular aneurysm (28), in which ventricular wall destruction by increased MMP activity is thought to be a main mechanism (29). It has also been shown that adenoviral transfer of the PAI-1 gene reduces tumor metastasis (30); in metastasis, extracellular matrix lysis is necessary for movement of transformed cells in tissues. In addition, Allaire et al have reported that, in a rat model of aortic aneurysm, blockade of PAs by local overexpression of PAI-1 prevents formation of aneurysms and arterial rupture by inhibiting MMP activation (9).…”
Section: Discussionmentioning
confidence: 99%
“…High expression of PAI-1 and uPA characterizes malignant astrocytic tumors (Yamamoto et al, 1994). Antisense against uPA or transfer of the PAI-1 gene reduced the invasiveness of glioma cells in vitro and decreased tumorigenicity (Praus et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Adenovirus-mediated delivery of anti-sense targeting uPAR induces the regression of pre-established glioblastoma tumors in vivo [105]. Although adenoviral transfer of PAI-1 reduces metastatic dissemination in mice with intraocular melanoma [120] or HT1080 tumors [121], the dose-dependent effect of PAI-1, pro-angiogenic at low concentration and antiangiogenic at higher ones [92,96] (Fig. 2), raises questions about the use of PAI-1 or PAI-1 antagonists for inhibition of tumoral angiogenesis.…”
Section: Delivery Of Viral Vectors To Suppress the Plasminogen Systemmentioning
confidence: 99%